2007
DOI: 10.1111/j.1532-950x.2007.00233.x
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Comparison of Surgical Ligation and Transarterial Catheter Occlusion for Treatment of Patent Ductus Arteriosus in Two Hundred and Four Dogs (1993–2003)

Abstract: Both SL and TCO are acceptable PDA treatments with comparable mortality; however, SL was associated with a higher risk of major complications and TCO was associated with a lower initial success rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
52
2
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(72 citation statements)
references
References 26 publications
2
52
2
6
Order By: Relevance
“…In other studies, survival was not affected by age >12 months at diagnosis, age >24 months at diagnosis, baseline FS ≤30%, weight, or the presence of residual flow at discharge 5, 18, 25. Dogs with clinical signs of heart failure have had variable outcomes reported including no effect on survival to more likely to have an unsuccessful ligation procedure and die perioperatively 18, 25. Likewise, the presence of MR at baseline evaluation has been associated with variable outcomes including no effect or a questionable effect on survival that did not reach significance in statistical analysis 5, 18.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…In other studies, survival was not affected by age >12 months at diagnosis, age >24 months at diagnosis, baseline FS ≤30%, weight, or the presence of residual flow at discharge 5, 18, 25. Dogs with clinical signs of heart failure have had variable outcomes reported including no effect on survival to more likely to have an unsuccessful ligation procedure and die perioperatively 18, 25. Likewise, the presence of MR at baseline evaluation has been associated with variable outcomes including no effect or a questionable effect on survival that did not reach significance in statistical analysis 5, 18.…”
Section: Discussionmentioning
confidence: 79%
“…Long‐term survival was negatively affected by age, weight, lethargy, preoperative treatment with angiotensin‐converting enzyme inhibitors, and right atrial enlargement on thoracic radiographs in a univariate analysis of 52 dogs 18. In other studies, survival was not affected by age >12 months at diagnosis, age >24 months at diagnosis, baseline FS ≤30%, weight, or the presence of residual flow at discharge 5, 18, 25. Dogs with clinical signs of heart failure have had variable outcomes reported including no effect on survival to more likely to have an unsuccessful ligation procedure and die perioperatively 18, 25.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In PDA with left-to-right shunting, a previous study showed that survival time was significantly longer in corrected dogs than in non-corrected dogs [31]. However, there was a insignificant difference in mortality between surgical ligation and transarterial coil occlusion in dogs with PDA [6,14]. Thus, surgical correction should be recommended as a radical treatment for PDA including surgical ligation, coil occlusion and an Amplatzer vascular plug [1,6,7,14,27].…”
Section: Discussionmentioning
confidence: 99%
“…In dogs with left-to-right shunting PDA, a previous study showed that survival time was significantly longer in corrected dogs than in non-corrected dogs [31]. Thus, correction of PDA including surgical ligation or transarterial coil occlusion should be recommended as early as possible after diagnosis [6,14].…”
mentioning
confidence: 99%